EXPLORING THE EFFECTIVENESS OF INTERACTIVE TECHNOLOGIES IN RUSSIAN LANGUAGE INSTRUCTION VIA ROLE-PLAYING GAMES (American Journal of Research in Humanities and Social Sciences, 2024)
The article examines the role of interactive technologies in teaching Russian as a foreign language, with an emphasis on the use of imitation (role-playing) games as an effective method to improve language skills and cultural understanding. The author emphasizes the importance of integrating modern educational approaches to create a dynamic and engaging learning environment that promotes the active participation of students in the educational process. Based on the analysis of theoretical foundations and practical examples, the article demonstrates how role-playing games supported by authentic materials and digital tools can significantly increase students' motivation, improve their communication skills and facilitate understanding of complex language structures through contextualized learning. The author discusses the methodology of developing and conducting role-playing games, including the preparation of scenarios, the selection of authentic materials, the use of technologies to ensure interactivity and strategies for evaluating student success.